Effect of priming interval on reactogenicity, peak immunological response, and waning after homologous and heterologous COVID-19 vaccine schedules: exploratory analyses of Com-COV, a randomised control trial - Shaw, RH; Liu, X; Stuart, ASV; Greenland, M; Aley, PK; Andrews, NJ; Cameron, JC; Charlton, S; Clutterbuck, EA; Collins, AM; Dejnirattisai, W; Dinesh, T; et al. (Elsevier, 2022)
Background Priming COVID-19 vaccine schedules have been deployed at variable intervals globally, which might influence immune persistence and the relative importance of third-dose booster programmes. Here, we report exploratory analyses from the Com-COV trial, assessing the effect of 4-week versus 12-week priming intervals on reactogenicity and the persistence of immune response up to 6 months after homologous and heterologous priming schedules using the vaccines BNT162b2 (tozinameran, Pfizer/BioNTech) and ChAdOx1 nCoV-19 (AstraZeneca).